The Influence of Taxpayer Knowledge, Taxpayer Awareness, Service Quality and Tax Sanctions on Personal Taxpayer Compliance In Kpp Pratama of Aceh Province - Dhikin, Hidayatussa; Nadirsyah, Nadirsyah; Darwanis, Darwanis (Devotion : Journal of Research and Community Service, 2023)
This study aims to examine the effect of taxpayer knowledge, taxpayer awareness, service quality and tax sanctions on individual taxpayer compliance. The sampel in this study were individual taxpayers registered at the Aceh Province Primary Tax Service Office (KPP). The sampling method used purposive sampling, and the sample size was measured using the Slovin formula. The data ananlysis technique in this study is descriptive statistics and multiple regression analysis using SPSS version 25. The results of hypothesis testing are as follow. Simultaneously, taxpayer knowledge, taxpayer awareness, service quality and tax sanctions affect individual taxpayer compliance. Partially, taxpayer knowledge, taxpayer awareness, service quality affect individual taxpayer compliance and tax sanctions have no effect on individual taxpayer compliance.